BOKO HARAM AND THE CHALLENGES OF INTERNAL SECURITY IN NIGERIA - ATTOH, FRANCA CHITOH (Advances in Social Sciences Research Journal, 2018)
Globally, the subject of national security is fundamental to the progress and development of the nation state. As a result, no nation treats with levity any problem that threatens its national security. The major thrust of this chapter is to assess the actions of Boko-haram and its implications on Nigeria's internal security. It takes a look at why insecurity remains a major challenge in Nigeria despite numerous efforts by the government to ensure the security of lives and property. It interrogates the phenomenon of Boko-haram and the myriad of challenges it poses to internal security in Nigeria. It analyzes the implications of terrorism which range from economic crises to political instability and above all food insecurity resulting in poverty and over two million internally displaced persons especially in the North-east of Nigeria. The author avers that Boko-haram insurgence has a spill-over effect to the countries in the West African sub-region (ECOWAS) thus enlarging the scope of insecurity. The data for the paper were sourced from interviews from military informants and secondary sources such as journals, magazines and internet resources. The author posits that the phenomenon of Boko-haram is as a result of the failure of the social contract and the absence of the process for conflict resolution in the post colonial state. Anchoring the analysis on the theory of Structural Functionalism and Karl Marx's Conflict theory it postulates that the phenomenon of Boko-haram is as a result of the failure of social contract resulting in normlessness and acute deprivation thus culminating in insecurity. It recommends among others, the need to empower the army of the unemployed, equip the security apparatti of the state, arrest and prosecute individuals found guilty of aiding and sponsoring insurgents. And initiate community policing to gather intelligence to stem the rising incidence of internal insecurity.